Zakat on one property if its character is various - An applied jurisprudential study- (Damascus University Journal for legal sciences, 2024)
Property is described as zakat property by falling under one of the categories of zakat properties specified by Sharia law, and that description may be multiple if property falls under more than one class of properties on which zakat is due. This is like someone who owns property that requires zakat in particular (such as crops, fruits, or livestock), and intends to trade with that property, so it becomes zakat property as well because it has become a trade goods. Are tow Zakats obligatory? Or zakat on crops, or livestock, for example? Or is he obligated to pay zakat on trade goods?The jurists unanimously agreed that two zakats should not be combined on one property at the same time, with the exception of some of them, such as the Shafi’is. Then they divided after that: the Hanafi and Shafi’is, according to the old school of thought, and the Hanbalis, according to the approved opinion, said that what is obligatory is zakat on trade, not zakat on property. On the other hand, the Malikis and Shafi’is , according to the new school of thought, went to the point that what is obligatory is zakat on property, not on trade.After reviewing the opinions of jurists and their evidence, the research concluded that the most likely opinion is the first opinion. Because it is more beneficial for the poor and more advantageous for them, then a contemporary application was studied, which is the issue: Zakat on shares falling under two categories of Zakat property; Such as shares of companies whose capital consists of agricultural products, or livestock, on which zakat is required in particular, and the intention of the shareholders is to trade in those shares.
Keywords: Zakat Funds; Property; Zakat On Property; Zakat